Open-air rock-art conservation and management
1 online resource (xvii, 297 pages)
Keywords: "While much has been achieved in understanding and managing weather effects and erosion phenomena affecting ancient imagery within the relatively protected environments of caves and rock-shelters, the same cannot be said of rock-art panels situated in the open-air. Despite the fact that the number of known sites has risen dramatically in recent decades there are few examples in which the weathering and erosion dynamics are under investigation with a view to developing proposals to mitigate the impact of natural and cultural processes. Most of the work being done in different parts of the world appears to be ad-hoc, with minimal communication on such matters between teams and with the wider archaeological community. This richly illustrated book evaluates rock-art conservation in an holistic way, bringing together researchers from across the world to share experiences of work in progress or recently completed. The chapters focus on a series of key themes: documentation projects and resource assessments; the identification and impact assessment of weathering/erosion processes at work in open-air rock-art sites; the practicalities of potential or implemented conservation interventions; experimentation and monitoring programs; and general management issues connected with public presentation and the demands of ongoing research investigations. Consideration is given to the conservation of open-air rock-art imagery from many periods and cultural traditions across the Old and New Worlds. This timely volume will be of interest to conservators, managers, and researchers dealing with aesthetic and ethical issues as well as technical and practical matters regarding the conservation of open-air rock-art sites."--